Solar cell module
Patent Information
- Application Number
- JP2023148241
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-26
AI Technical Summary
【0017】 本発明の太陽電池モジュールによれば、高い反射ヘイズで、かつ、変換効率の低下が抑制された太陽電池モジュールを提供できる。
Smart Images

Figure 2025041135000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a solar cell module. [Background technology]
[0002] When installing solar cell modules on a building, they may be installed not only on the roof but also on the wall surface, etc., in order to increase the amount of power generated. In this case, the surface of the solar cell module is usually black, which causes a problem in terms of appearance.
[0003] It has been proposed to form a colored covering layer on a glass substrate disposed on the light-receiving surface side of a solar cell module to color the exterior of the solar cell module (see Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2017 / 090056 Summary of the Invention [Problem to be solved by the invention]
[0005] However, when the exterior of a solar cell module is colored, the color is reflected, preventing light from reaching the solar cell module, resulting in a problem of reduced conversion efficiency.
[0006] The present invention has been made in consideration of the above circumstances, and has an object to provide a solar cell module that has high reflective haze and suppresses a decrease in conversion efficiency. [Means for solving the problem]
[0007] In order to solve the above problems, the present invention provides the following means.
[0008] A first aspect of the present invention is a solar cell module comprising: a substrate; a power generation layer disposed on the substrate and having solar cells and a sealant layer surrounding at least the top and side surfaces of the solar cells; and a transparent substrate disposed on the power generation layer and having a microfibrillated cellulose-containing film formed directly on the surface facing the power generation layer.
[0009] A second aspect of the present invention is a solar cell module according to the first aspect, wherein the solar cell module has a reflective haze of 30% or more and a transmittance of 60% or more for light perpendicularly incident on the transparent substrate in a range of 380 nm to 700 nm. Here, reflective haze [%] = {Rd / Rt} × 100 (Rd is diffuse reflection, Rt is total reflection).
[0010] A third aspect of the present invention is the solar cell module of the second aspect, wherein the lightness in the Munsell color system is 20 or more.
[0011] A fourth aspect of the present invention is the solar cell module of the third aspect, wherein the microfibrillated cellulose contained in the microfibrillated cellulose-containing film has an average fiber diameter of 5 nm or more.
[0012] A fifth aspect of the present invention is the solar cell module of the fourth aspect, wherein the average fiber diameter is 10 nm or more and 100 nm or less.
[0013] A sixth aspect of the present invention is the solar cell module of the fifth aspect, wherein the average fiber diameter is 30 nm or more and 70 nm or less.
[0014] A seventh aspect of the present invention is a solar cell module according to any one of the fourth to sixth aspects, wherein the microfibrillated cellulose contained in the microfibrillated cellulose-containing film has no functional group on its side chain.
[0015] An eighth aspect of the present invention is the solar cell module of the seventh aspect, wherein the amount of lignin and hemicellulose contained in the microfibrillated cellulose-containing film is 10% or less.
[0016] A ninth aspect of the present invention is the solar cell module of the eighth aspect, wherein the microfibrillated cellulose-containing film contains one or more types of cellulose derivatives. Effect of the Invention
[0017] According to the solar cell module of the present invention, it is possible to provide a solar cell module having high reflective haze and suppressing a decrease in conversion efficiency. [Brief description of the drawings]
[0018] [Figure 1] 1 is a schematic cross-sectional view of a solar cell module according to an embodiment of the present invention. [Diagram 2] 2 is a schematic cross-sectional view of a modified example of the solar cell module shown in FIG. [Diagram 3] 1 is a histogram showing the fiber diameter distribution of microfibrillated cellulose in the MFC-containing membrane of Sample 1. [Figure 4] 1 is a histogram showing the fiber diameter distribution of microfibrillated cellulose in the MFC-containing membrane of sample 2. [Diagram 5] 1 is a histogram showing the fiber diameter distribution of microfibrillated cellulose in the MFC-containing membrane of sample 3. [Figure 6] Graphs showing the optical properties of the raw glass used in the sample, where (a) is the reflectance spectrum, (b) is the transmission spectrum, and (c) is the reflection haze spectrum. [Figure 7] 1 is a graph showing the optical characteristics of Sample 4 (Comparative Example), where (a) is the reflection spectrum, (b) is the transmission spectrum, and (c) is the reflection haze spectrum. [Figure 8] 1 is a graph showing the optical characteristics of Sample 1 (Example 1), where (a) is the reflection spectrum, (b) is the transmission spectrum, and (c) is the reflection haze spectrum. [Figure 9] 5 is a graph showing the optical characteristics of Sample 2 (Example 2), where (a) is the reflection spectrum, (b) is the transmission spectrum, and (c) is the reflection haze spectrum. [Figure 10]5 is a graph showing the optical characteristics of Sample 3 (Example 3), where (a) is the reflection spectrum, (b) is the transmission spectrum, and (c) is the reflection haze spectrum. [Figure 11] 1 is a graph showing the relationship between fiber diameter and lightness L*(45) for Samples 1 to 4. [Figure 12] 1 is a graph showing the results of measuring the percentage reduction in short-circuit current density ΔJsc (%) calculated from the short-circuit current density measured when Samples 1 to 4 were placed on a solar cell and the short-circuit current density measured when a glass substrate without an MFC-containing film was placed on a solar cell. [Figure 13] 1 is a graph showing the relationship between lightness L*(45) and ΔJsc (%) of a sample to which CMC was added. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present invention will be described in detail below with reference to the drawings as appropriate. The drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the features of the present invention easier to understand, and the dimensional ratios of each component may differ from the actual ones. The materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not limited thereto. The present invention can be practiced by appropriately changing them within the scope of the effects of the present invention. Furthermore, even if a configuration is described only in one embodiment, it can be practiced by appropriately applying it to another embodiment.
[0020] FIG. 1 is a schematic cross-sectional view of a solar cell module according to this embodiment. The solar cell module 100 shown in FIG. 1 comprises a substrate 10, a power generation layer 50 arranged on the substrate 10 and having solar cells 20 and a sealing material layer 30 surrounding the upper surface 20A and the side surface 20B of the solar cells 20, and a transparent substrate 80 arranged on the power generation layer 50 and having a microfibrillated cellulose-containing film 70 formed directly on the surface 50A facing the power generation layer 50.
[0021] In this specification, the term "solar cell module" refers to a known configuration, and a representative configuration is one in which multiple solar cells are arranged and sealed using a support plate, a sealing material, and a backing material (back sheet), and then an outer frame is fitted to provide overall strength depending on the place of use, and sealed for the purposes of fixing and preventing condensation, etc. Therefore, in addition to the components shown in Fig. 1, known components may be included.
[0022] Although wiring and the like are omitted from the solar cell module 100 shown in FIG. 1, a known wiring structure can be used.
[0023] In the solar cell module 100 shown in FIG. 1, the lower surface 20C (see FIG. 2) of the solar cell 20 is directly disposed on the upper surface 10A of the substrate 10. However, as in the solar cell module 101 shown in FIG. 2, the solar cell module may have a power generation layer 51 in which the upper surface 20A, the side surface 20B and the lower surface 20C of the solar cell 20 are all surrounded by a sealing material layer 30.
[0024] The solar cell module of this embodiment can use any known configuration used in solar cell modules, except for the transparent substrate 80 having the microfibrillated cellulose-containing film 70 formed directly on the surface 50A on the power generation layer 50 side.
[0025] <Substrate> There are no particular limitations on the substrate 10 as long as it is an insulating substrate. The substrate 10 is not limited to a single unit, but may be a laminate of a plurality of plates, sheets, or layers. The substrate 10 may be any of various glass plates.
[0026] The substrate 10 may be a known back sheet itself, or may be composed of a back sheet and a supporting substrate disposed on the side of the sealing material layer 30. Various glass plates can be used as the supporting substrate. The use of a backsheet improves power generation efficiency because the backsheet reflects light that passes through the gaps between solar cells and light that has been transmitted through the solar cells, allowing the sunlight to enter the solar cells again.
[0027] In addition to electrical insulation, the substrate 10 and the members constituting the substrate 10 (for example, the back sheet and the supporting substrate) preferably have weather resistance, water vapor barrier properties, mechanical properties, chemical resistance, etc. Also, it is preferable that the substrate 10 has good adhesion to the sealing material layer 30.
[0028] <Transparent substrate> As the transparent substrate 80, a known transparent substrate capable of transmitting light in the visible light range is used, such as various glass plates, plastic plates made of polycarbonate resin, acrylic resin, etc., inorganic transparent plates made of transparent inorganic materials other than glass, mica plates, etc.
[0029] The transparent substrate 80 has a thickness of, for example, 0.1 mm to 10 mm.
[0030] The transparent substrate 80 preferably has a transmittance of 80% or more, and more preferably has a transmittance of 90% or more.
[0031] <Microfibrillated cellulose-containing membrane> The microfibrillated cellulose-containing film 70 is formed directly on a transparent substrate 80 . In this specification, the term "directly formed into a film" refers to a state in which an aqueous dispersion containing microfibrillated cellulose is spread on the transparent substrate 80, and then dried to be fixed on the transparent substrate 80 to form a film. The method of "spreading" is arbitrary, and can be a known method such as dropping, applying, scattering, or spraying with a spray. A dispersion in which microfibrillated cellulose is dispersed in an organic solvent, such as ethanol or butanol, may also be used. The microfibrillated cellulose-containing film 70 thus formed on the transparent substrate is integrated with the transparent substrate 80, and therefore has higher adhesion and is less prone to wrinkles than a structure in which the film is attached to the transparent substrate as a separate member (for example, as paper or a sheet). As a result, a high reflection haze and reduced degradation of conversion efficiency are achieved at the same time.
[0032] The transparent substrate 80 on which the microfibrillated cellulose-containing film 70 is directly formed preferably has a reflection haze of 30% or more and a transmittance of 60% or more for perpendicularly incident light in the range of 380 nm to 700 nm. The reflection haze is more preferably 40% or more and even more preferably 50% or more in the range of 380 nm to 700 nm. The transmittance is more preferably 70% or more and even more preferably 80% or more. Here, the reflective haze can be calculated, for example, by using an integrating sphere to measure total reflection, including specular reflection and diffuse reflection, and only diffuse reflection, as follows: reflective haze [%] = {Rd / Rt} × 100 (Rd is diffuse reflection, Rt is total reflection).
[0033] Furthermore, the microfibrillated cellulose-containing membrane 70 is disposed on the surface of the transparent substrate 80 on the power generation layer 50 side, and is sealed with the sealing material layer 30. Therefore, deterioration over time is suppressed.
[0034] In this specification, the "microfibrillated cellulose (MFC)" contained in the microfibrillated cellulose-containing membrane 70 refers to cellulose fibers having an average fiber diameter of 5 nm or more that have been defibrated only by physical treatment in water without chemical treatment. The aqueous dispersion containing microfibrillated cellulose is cloudy. The microfibrillated cellulose contained in the microfibrillated cellulose-containing membrane 70 has been defibrated in water only by physical treatment, and therefore has no functional groups on its side chains.
[0035] Examples of the range of the fiber diameter of the MFC contained in the microfibrillated cellulose-containing membrane 70 include 10 nm to 300 nm, 10 nm to 100 nm, and 50 nm to 300 nm. The three examples 1, 2, and 3 described below are examples in which the proportion of MFC fiber diameters contained in the microfibrillated cellulose-containing membrane 70 that is in the range of 15 nm to 50 nm is approximately 80%, an example in which the proportion of MFC fiber diameters that is in the range of 15 nm to 120 nm is approximately 90%, and an example in which the proportion of MFC fiber diameters that is in the range of 8 nm to 100 nm is approximately 95%. Therefore, in this specification, "cellulose nanofibers (CNF)" with an average fiber diameter of less than 5 nm do not correspond to "microfibrillated cellulose (MFC)" contained in the microfibrillated cellulose-containing membrane 70. Therefore, for example, "cellulose nanofibers (CNF)" with an average fiber diameter of about 3 to 4 nm do not correspond to "microfibrillated cellulose (MFC)" contained in the microfibrillated cellulose-containing membrane 70. In addition, "cellulose nanofibers (CNF)" produced by introducing electric charge to the microfibril surface to uniformly disperse do not correspond to "microfibrillated cellulose (MFC)" contained in the microfibrillated cellulose-containing membrane 70. In addition, "cellulose nanofibers (CNF)" accompanied by phosphate esterification, phosphite esterification, sulfate esterification, xanthate esterification, carboxymethyl etherification, dicarboxycellulose oxidation, etc. do not correspond to "microfibrillated cellulose (MFC)" contained in the microfibrillated cellulose-containing membrane 70.
[0036] The amount of lignin and hemicellulose contained in the microfibrillated cellulose-containing membrane 70 is preferably 10% or less. Wood contains three types of components: microfibrillated cellulose, lignin, and hemicellulose. By reducing the amount of components other than microfibrillated cellulose, it is possible to prevent a decrease in reliability due to exposure to ultraviolet (UV) rays.
[0037] It is preferable that the microfibrillated cellulose-containing film 70 contains one or more cellulose derivatives. Examples of the one or more cellulose derivatives can be selected from the group consisting of polymers such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, and the like. This is because the transmittance is improved, and as a result, a decrease in conversion efficiency can be suppressed.
[0038] CMC is an anionic water-soluble polymer obtained from cellulose as a raw material and has thickening properties. When dissolved in an aqueous sodium chloride solution, the viscosity can be increased.
[0039] <Sealing agent layer> As the sealing agent layer 30, a known material such as a transparent resin can be used.
[0040] <Solar cell> As the solar cell 20, a known type of solar cell can be used. For example, from the viewpoint of electrode arrangement, either a double-sided electrode type solar cell or a back electrode type solar cell can be used. Also, from the viewpoint of classifying solar cells into silicon-based, compound semiconductor-based, and organic-based, there is no particular limitation, and any type of solar cell can be used.
[0041] <Solar cell module> The solar cell module 100 can be used for various applications. For example, it can be installed on the wall surface of a building or the like, or attached to the outer plate of a moving body such as an automobile, bus, train, or bicycle, or various display boards such as traffic signs, billboards, and bulletin boards.
[0042] <Method for producing a transparent substrate on which an MFC-containing film is directly formed> An example of a method for producing a transparent substrate on which a microfibrillated cellulose (MFC)-containing film is directly formed is illustrated below.
[0043] First, the MFC in a water-dispersed state is adjusted to 2 wt% or less and stirred at room temperature (the first step). Instead of the MFC in the water dispersion state, a dry MFC may be used. From the viewpoint of the efficiency of the solar cell, the amount of MFC is preferably 2 wt % or less. When preparing an MFC-containing membrane that contains CMC, etc., in the first step, it is mixed with 2 wt % or less of a CMC solution.
[0044] Next, the dispersion liquid is dropped onto a glass substrate (transparent substrate) in a dryer (second step).
[0045] After the dispersion liquid is dropped, the mixture is left at 30° C. for about 24 hours until the dispersion liquid is completely dried (third step). In this manner, a glass substrate (transparent substrate) on which an MFC-containing film is directly formed can be obtained. EXAMPLES
[0046] [Preparation of Samples 1 to 3] Microfibrillated cellulose (MFC) in a water dispersion state was adjusted to 2 wt%, and stirred at room temperature for 30 minutes to obtain an MFC dispersion. The obtained MFC dispersion was then dropped onto a glass plate with a visible light wavelength transmittance of 92%. After dropping the MFC dispersion, it was left at 30°C for about 24 hours until the dispersion was completely dried. In this way, a glass plate sample was prepared having a microfibrillated cellulose (MFC)-containing membrane deposited directly on one side.
[0047] Example 1 Fig. 3 shows the fiber diameter distribution of microfibrillated cellulose in the MFC-containing membrane measured from the SEM image obtained for Sample 1 used in Example 1. In Fig. 3, the horizontal axis represents fiber diameters at 5 nm intervals, and the vertical axis is a histogram showing the number of fiber diameters in each 5 nm range, showing the distribution of fiber diameters at 5 nm intervals of microfibrillated cellulose in the MFC-containing membrane. The MFC-containing membrane of sample 1 was composed of 90% or more microfibrillated cellulose with a fiber diameter of 10 to 100 nm, approximately 80% microfibrillated cellulose with a fiber diameter of 15 to 50 nm, and had an average fiber diameter of 41 nm.
[0048] Example 2 FIG. 4 shows the fiber diameter distribution of the MFC-containing membrane measured from the SEM image obtained for Sample 2 used in Example 2. The MFC-containing membrane of sample 2 contained 95% or more microfibrillated cellulose with a fiber diameter of 15 to 300 nm, approximately 90% microfibrillated cellulose with fiber diameters of 15 to 60 nm and 80 to 120 nm, and the average fiber diameter was 56 nm.
[0049] Example 3 FIG. 5 shows the fiber diameter distribution of the MFC-containing membrane measured from the SEM image obtained for Sample 3 used in Example 3. The MFC-containing membrane of sample 3 was composed of 95% or more microfibrillated cellulose with a fiber diameter of 8 to 100 nm, approximately 80% microfibrillated cellulose with a fiber diameter of 8 to 38 nm, and had an average fiber diameter of 34 nm.
[0050] (Comparative Example) Sample 4 used as a comparative example was prepared in the same manner as the above-mentioned Samples 1 to 3, except that cellulose nanofibers (CNF) were used instead of microfibrillated cellulose. That is, Sample 4 is a glass plate having a cellulose nanofiber (CNF)-containing film formed directly on one surface. The CNFs used had a uniform fiber diameter of 3 to 4 nm and fiber lengths of several hundred nm to 1 μm.
[0051] [Optical properties] The reflection and transmission characteristics were measured using an ultraviolet-visible-near infrared spectrophotometer V-670 (manufactured by JASCO Corporation). The measurement light was incident perpendicularly on the side of the sample that did not have the MFC- or CNF-containing film. The solar cell module according to this embodiment preferably has a reflection haze of 30% or more and a transmittance of 60% or more in the range of 380 nm to 700 nm for light perpendicularly incident on the transparent substrate.
[0052] Figure 6 shows the optical properties of the glass plate used. Figure 6(a) shows the reflection spectrum, (b) shows the transmission spectrum, and (c) shows the reflection haze spectrum. In the graph, Rt is the total reflectance, Rd is the diffuse reflectance, Rs is the specular reflectance, Tt is the total transmittance, Td is the diffuse transmittance, and Tp is the parallel transmittance. It can be seen that for light with wavelengths in the visible light range, the transmittance is 91 to 92%, and the reflection haze is 3% or less.
[0053] Fig. 7 shows the optical characteristics of Sample 4 (Comparative Example). Fig. 7(a) shows the reflection spectrum, (b) shows the transmission spectrum, and (c) shows the reflection haze spectrum. Rp is the specular reflectance. It can be seen that for light with wavelengths in the visible light range, the transmittance is about 90% and the reflective haze is about 10%.
[0054] Fig. 8 shows the optical characteristics of Sample 1 (Example 1). Fig. 8(a) shows the reflection spectrum, (b) shows the transmission spectrum, and (c) shows the reflection haze spectrum. Rp is the specular reflectance. It can be seen that for light with wavelengths in the visible light range, the transmittance is about 70% and the reflective haze is about 50%.
[0055] 9 shows the optical characteristics of Sample 2 (Example 2). Fig. 9(a) shows the reflection spectrum, (b) shows the transmission spectrum, and (c) shows the reflection haze spectrum. Rp is the specular reflectance. It can be seen that for light with wavelengths in the visible light range, the transmittance is about 70% and the reflective haze is about 50%.
[0056] Fig. 10 shows the optical characteristics of Sample 3 (Example 3). Fig. 10(a) shows the reflection spectrum, (b) shows the transmission spectrum, and (c) shows the reflection haze spectrum. Rp is the specular reflectance. It can be seen that for light with wavelengths in the visible light range, the transmittance is about 85% and the reflective haze is about 70%.
[0057] [Whiteness (lightness)] Whiteness (lightness) L *(45) was measured using a spectrophotometer CM-M6 (Konica Minolta, Inc.). * (45) is the brightness measured using an optical system with 45° incidence and 90° reception. FIG. 11 shows the lightness L in the Munsell color system on the horizontal axis for Samples 1 to 4. * (45), the vertical axis shows the fiber diameter (nm) in logarithm and the lightness L * 45] The solar cell module according to this embodiment has a lightness L * It is preferable that (45) is 20 or more. Lightness L * It can be seen that in order to make (45) 20 or more, the average fiber diameter of the MFC contained in the MFC-containing membrane needs to be 5 nm or more.
[0058] [Conversion efficiency] Samples 1 to 4 were placed on a solar cell, and the short-circuit current density Jsc (the current that flows when the external voltage applied to the solar cell is 0 V) was measured (this current density is referred to as Jsc (with MFC)). In addition, a glass substrate without an MFC-containing film was placed on the solar cell, and the short-circuit current density Jsc was measured (this current density is referred to as Jsc (without MFC)). Next, the reduction rate of the current density, ΔJsc (%), which is an index for evaluating the efficiency of the solar cell, was calculated by the following formula: [{Jsc(without MFC) - Jsc(with MFC)} / Jsc(without MFC)]×100
[0059] FIG. 12 shows the results of calculating the reduction ratio ΔJsc (%) for each of Samples 1 to 4. From FIG. 12, it can be seen that in both Samples 1 and 2, ΔJsc (%) is suppressed to about 16 to 17%, and in Sample 3, ΔJsc (%) is suppressed to about 5%.
[0060] [Effect of adding CMC] A dispersion obtained from 5 g of MFC, 15 g of sodium carboxymethylcellulose (CMC-Na), and 10 g of water used in Sample 1 was applied to a glass plate with a visible light wavelength transmittance of 92%, and the dispersion was left at 30°C for about 24 hours until it was completely dried, producing Sample 1A, a glass plate having an MFC-containing film containing CMC-Na formed directly on one side. Also, using the dispersion obtained from 5 g of MFC and 25 g of water used in Sample 1, Sample 1-1, a glass plate having a microfibrillated cellulose (MFC)-containing film formed directly on one side, was produced as described above.
[0061] FIG. 13 shows the lightness L of Sample 1-1 and Sample 1A. * (45) and ΔJsc (%) are measured.
[0062] A dispersion obtained from 10 g of MFC, 10 g of sodium carboxymethylcellulose (CMC-Na), and 10 g of water used in Sample 1 was applied to a glass plate with a visible light wavelength transmittance of 92%, and the dispersion was left at 30°C for about 24 hours until it was completely dried, producing Sample 1B, a glass plate having an MFC-containing film containing CMC-Na formed directly on one side. Also, using the dispersion obtained from 10 g of MFC and 20 g of water used in Sample 1, Sample 1-2, a glass plate having a microfibrillated cellulose (MFC)-containing film formed directly on one side, was produced as described above.
[0063] For Sample 1-2 and Sample 1B, L * (45) and ΔJsc (%) are measured.
[0064] As shown in FIG. 13, the addition of CMC-Na increased the L * (45) decreases, but the conversion efficiency improves (ΔJsc (%) decreases). This is thought to be the result of the addition of CMC increasing the viscosity, making it easier to apply. Depending on the amount of CMC, L * (45) and ΔJsc (%) can be adjusted. [Explanation of symbols]
[0065] 10 Substrate 20 Solar Cells 30 Encapsulant layer 50, 51 Power generation layer 70 Microfibrillated cellulose-containing membrane 80 Transparent Substrate 100, 101 Solar cell module
Claims
1. A substrate; a power generation layer disposed on the substrate and having a solar cell and a sealing material layer surrounding at least an upper surface and a side surface of the solar cell; A solar cell module comprising: a transparent substrate disposed on a power generation layer and having a microfibrillated cellulose-containing film formed directly on the surface facing the power generation layer.
2. 2. The solar cell module according to claim 1, wherein the transparent substrate has a reflection haze of 30% or more and a transmittance of 60% or more in a range of 380 nm to 700 nm for light perpendicularly incident on the transparent substrate; Here, reflective haze [%]={Rd / Rt}×100 (Rd is diffuse reflection, and Rt is total reflection).
3. 3. The solar cell module according to claim 2, having a value of 20 or more in the Munsell color system.
4. The solar cell module according to claim 1 , wherein the microfibrillated cellulose contained in the microfibrillated cellulose-containing film has an average fiber diameter of 5 nm or more.
5. The solar cell module according to claim 4 , wherein the average fiber diameter is 10 nm or more and 100 nm or less.
6. The solar cell module according to claim 5 , wherein the average fiber diameter is 30 nm or more and 70 nm or less.
7. The solar cell module according to any one of claims 4 to 6, wherein the microfibrillated cellulose contained in the microfibrillated cellulose-containing membrane has no functional groups on its side chains.
8. The solar cell module according to claim 7 , wherein the amount of lignin and hemicellulose contained in the microfibrillated cellulose-containing film is 10% or less.
9. The solar cell module according to claim 8 , wherein the microfibrillated cellulose-containing membrane comprises one or more cellulose derivatives.
Citation Information
Patent Citations
Solar module with selective colored coating
WO2017090056A1